Goldenhar Syndrome - A Case Report - Siddique, MAR; Hossain, J; Abedin, MJ; Parvez, M (Journal of Bangladesh College of Physicians and Surgeons, 2010)
A 7 years old boy was diagnosed a case of Goldenhar Syndrome. He presented with swelling in the upper and outer part of the left eye as limbal dermoid associated with preauricular tags, hemifacial asymmetry, microtia and small chin since birth. His vertebral anomalies also detected by skiagram of the vertebral column as spina bifida. His ocular and auricular problems were solved by surgery without any complicatons. Patient is leading a normal life. DOI: 10.3329/jbcps.v28i3.6515 J Bangladesh Coll Phys Surg 2010; 28: 193-195